Relative susceptibility of the Bikaner and Delhi populations of mustard aphid, Lipaphis erysimi (Kalt.) (Homoptera: Aphididae), and its predator, Coccinella septempunctata L. (Coleoptera: Coccinellidae), to different insecticides - Shankarganesh, K.; Suroshe, Sachin; Paul, Bishwajeet (Phytoprotection, 2015)
A study was undertaken to assess the effectiveness of five insecticides against the Delhi and Bikaner populations of mustard aphid, Lipaphis erysimi (Kalt.), using the leaf dip method, and against Coccinella septempunctata L. in semi-field conditions. Acetamiprid and thiamethoxam were found to be more toxic than other insecticides. After 24 h, the LC50 values for the Bikaner population against different insecticides were 7.0, 6.0, 4.0, 3.0 and 2.0 ppm for carbosulfan, bifenthrin, imidacloprid, acetamiprid and thiamethoxam, respectively. Similarly, the descending order of toxicity for the Delhi population was acetamiprid (7.0 ppm), thiamethoxam (9.0 ppm), imidacloprid (15.0 ppm), carbosulfan (32.0 ppm) and bifenthrin (36.0 ppm). The relative toxicity values suggest that in both populations, thiamethoxam and acetamiprid show the highest toxicity. Carbosulfan and bifenthrin were highly toxic to coccinellid grubs and resulted in 100% mortality in semi-field conditions, whereas the neonicotinoids acetamiprid and thiamethoxam showed less mortality. It showed the tolerance of coccinellidae against neonicotinoids under semi-field conditions.